Bioprotective properties of seaweeds: In vitro evaluation of antioxidant activity and antimicrobial activity against food borne bacteria in relation to polyphenolic content - Kesika Periyanaina; Suganthy Natarajan; Devi Kasi; Pandian Shanmugaiahthevar (BMC, 2008)
Abstract Background For many years chemical preservatives have been used in food, to act as either antimicrobials or antioxidants or both. In general, consumers regard additive-free foods as safer since preservatives can cause health hazards like asthma and cancer and are suspected to be mutagenic and neurotoxic. The present study was carried out to evaluate the antimicrobial and antioxidant activity of methanolic extracts of seaweeds, with a view to developing safer food preservatives. Methods Ten edible seaweeds, which have wide pharmaceutical application, were collected from Central Marine Fisheries Research Institute, Tamil Nadu, India and evaluated for antioxidant and antimicrobial activity against food borne pathogens. Results The results indicate that Gelidiella acerosa has the highest antioxidant activity while Haligra sps exhibited antibacterial activity against Staphylococcus aureus (MTCC 96). Conclusion Quantitative analysis of the total phenolic content of the seaweeds indicated that Gelidella acerosa and Haligra sps have high phenolic contents, which correlated to their respective antioxidant and antimicrobial activity